The Evolution of Peteroa Volcano (Chile–Argentina) Crater Lakes Between 1984 and 2020 Based on Landsat and Planet Labs Imagery Analysis - Aguilera, Felipe; Caro, Javiera; Layana, Susana (Frontiers in Earth Science, 2021)
One of the major challenges in the understanding of the crater lakes dynamics and their connection with magmatic/hydrothermal processes is the continuous tracking of the physical behavior of lakes, especially in cases of remote and poorly accessible volcanoes. Peteroa volcano (Chile–Argentina border) is part of the Planchón–Peteroa–Azufre Volcanic Complex, one of the three volcanoes in the Southern Volcanic Zone of the Andes with crater lakes. Peteroa volcano is formed by a ∼5 km diameter caldera-type crater, which hosts four crater lakes and several fumarolic fields. Peteroa volcano has a large history of eruptive activity including phreatic-and-phreatomagmatic explosions and several episodes of strong degassing from its crater lakes. Here, we used TIR and SWIR bands from Landsat TM, ETM+, and OLI images available from October 1984 to December 2020 to obtain thermal parameters such as thermal radiance, brightness temperature, and heat fluxes, and Planet Labs Inc. images (RapidEye and PlanetScope) available between May 2009 and December 2020 to obtain physical parameters such as area, color, and state (liquid or frozen) of the crater lakes. We reviewed the historical eruptive activity and compared it with thermal and physical data obtained from satellite images. We determined the occurrence of two eruptive/thermal cycles: 1) Cycle 1 includes the formation of a new fumarolic field and two active craters during a short eruptive period, which includes thermal activity in three of the four crater lakes, and a strong degassing process between October 1998 and February 2001, coincident with a peak of volcanic heat flux (Qvolc) in two craters. The cycle finished with an eruptive episode (September 2010–July 2011). 2) Cycle 2 is represented by the thermal reactivation of two crater lakes, formation and detection of thermal activity in a new nested crater, and occurrence of a new eruptive episode (October 2018–April 2019). We observed a migration of the thermal and eruptive activity between the crater lakes and the interconnection of the pathways that feed the lakes, in both cases, partially related to the presence of two deep magma bodies. The Qvolc in Peteroa volcano crater lakes is primarily controlled by volcanic activity, and seasonal effects affect it at short-term, whilst at long-term, seasonal effects do not show clear influences in the volcanic heat fluxes. The maximum Qvolc measured between all crater lakes during quiescent periods was 59 MW, whereas during unrest episodes Qvolc in single crater lakes varied from 7.1 to 38 MW, with Peteroa volcano being classified as a low volcanic heat flux system. The detection of new thermal activity and increase of Qvolc in Peteroa volcano previous to explosive unrest can be considered as a good example of how thermal information from satellite images can be used to detect possible precursors to eruptive activity in volcanoes which host crater lakes.